UJI TOKSISITAS KOLOWE (Chydenanthus excelsus, Miers) DENGAN MENGGUNAKAN METODE BSLT (Brine Shrimp Lethality Test) - HENNY HELMI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2008)
A research to find out the toxicity of kolowe seeds on Artemia salina had been done. Crude extract and fractions of kolowe seeds contain saponin, alkaloid, polifenol and triterpenoid. Based on their antibacteria and antifungi activities, kolowe seeds can be used as biopesticide. Toxicity test against to Brine shrimp has been done to know the safety of this biopesticide. The results showed that kolowe seeds extract and fractions had a low toxicity on Artemia salina (LC50 > 30 ppm). In conclusion, kolowe seeds can be an alternative to be used as biopesticide